SCIENCE INTEGRATION IN ISLAM - Fatkhur Rohman (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this article aims to describe and analyze the science integration in Islam. The intended science integration is a condition in which one science with another is not mixed, so that it loses its ontology, epistemology and axiology, but an effort to synergize, dialogue, communicate, and bring together, so that between the sciences there is a common ground, and devoted not only to the interests of science itself, but according to its main function, namely to provide light, explanation, convenience and guidance for humans in responding to various phenomena of life. This study actually started a long time ago, but until now it is still not finished so that in practice the Islamic higher education institutions each have different formulations and models in the implementation of the integration of this knowledge. The method in this study uses a library method or approach (library research). Literature study can be interpreted as an effort to collect research data through notes, transcripts, books, newspapers, magazines, journals and so on.Keywords: Science Integration and Science Integration Model at Islamic Education Institution